2006
DOI: 10.1097/01.wnr.0000230500.03330.01
|View full text |Cite
|
Sign up to set email alerts
|

White matter abnormalities in dystonia normalize after botulinum toxin treatment

Abstract: The pathophysiology of dystonia is still poorly understood. We used diffusion tensor imaging to screen for white matter abnormalities in regions between the basal ganglia and the thalamus in cervical and hand dystonia patients. All patients exhibited an abnormal hemispheric asymmetry in a focal region between the pallidum and the thalamus. This asymmetry was absent 4 weeks after the same patients were treated with intramuscular botulinum toxin injections. These findings represent a new systems-level abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 26 publications
9
67
2
1
Order By: Relevance
“…In CD, DTI abnormalities in the putamen, caudate head, pallidum, prefrontal cortex, SMA, and corpus callosum have been previously demonstrated. [19][20][21][22] In patients with focal hand dystonia, VBM data receive support from the recent finding of DTI abnormalities in the fiber tracts connecting the primary sensorimotor areas with subcortical structures. 23 The reduced connectivity reported in the subcortical white matter of the sensorimotor area in DYT1 mutation carriers 24 further supports the axonal loss in this subcortical white matter region and abnormalities in the neuronal density in the overlying cortex, which may contribute to the development of dystonia.…”
Section: Discussionmentioning
confidence: 85%
“…In CD, DTI abnormalities in the putamen, caudate head, pallidum, prefrontal cortex, SMA, and corpus callosum have been previously demonstrated. [19][20][21][22] In patients with focal hand dystonia, VBM data receive support from the recent finding of DTI abnormalities in the fiber tracts connecting the primary sensorimotor areas with subcortical structures. 23 The reduced connectivity reported in the subcortical white matter of the sensorimotor area in DYT1 mutation carriers 24 further supports the axonal loss in this subcortical white matter region and abnormalities in the neuronal density in the overlying cortex, which may contribute to the development of dystonia.…”
Section: Discussionmentioning
confidence: 85%
“…The white matter asymmetry observed in the ansa lenticularis of dystonia patients before treatment may have reflected activitydependent microstructural changes in the projection fibers of neurons exhibiting abnormal activity. According to the authors, it is unlikely that the observed normalisation after BoNT treatment is a permanent change, because the asymmetries that were observed after earlier BoNT injections were not associated with clinical effectiveness (Blood et al, 2006).…”
Section: Diffusion-tensor Imagingmentioning
confidence: 99%
“…It may be speculated that defective or deficient torsinA could disrupt normal structural relationships between neurons and glia. Microstructural changes have been identified in white matter in DYT1 mutation carriers with diffusion tensor magnetic resonance imaging (DT-MRI) (Carbon et al, 2004;Blood et al, 2006). Fractional anisotropy (FA), a measure of axonal integrity and coherence, was significantly reduced in the white matter underlying sensorimotor cortex in DYT1 mutant carriers (Carbon et al, 2004).…”
Section: Torsina Structure and Functionmentioning
confidence: 99%